My Father's Wake How the Irish Teach us to Live, Love and Die - Toolis, Kevin (London : Weidenfeld & Nicolson, 2018)
On a remote island, off the coast of County Mayo, along with reports of incoming Atlantic storms, the local radio station runs a thrice-daily roll-call of the recently departed. The islanders have no fear of death. They go in great numbers, often with young children, to wake with their dead. They keep vigil through the night with the corpse and share in the sorrow of the bereaved. They bear the burden of the coffin on their shoulders and dig the grave with their own hands. The living and the dead remain bound together in the Irish Wake - the oldest rite of humanity. For 20 years writer and filmmaker Kevin Toolis hunted death in famine, war and plague across the world before finding the answer to his quest on the island of his forebears.
Originally published: 2017.
Keywords: Toolis, Kevin -- Family; Wake Services -- Ireland; Funeral rites and ceremonies -- Ireland; Family and Relationships